SERVICE QUALITY AND CONSUMER PROTECTION LAWS IN THE PARKING INDUSTRY: AN IMPLICATIONS FOR CONSUMER SATISFACTION - Husin Wattimena; Arizal Hamizar; Hasan; H. Rajab (PT. Antis International Publisher, 2024)
The examination of consumer protection laws in the parking sector in Ambon constitutes the primary focus of this study, emphasizing the breaches in service quality that result in customer discontentment and unfavorable perceptions of service provision. Employing the SERVQUAL framework, the study delves into the identification of the five pivotal dimensions of service quality pivotal to customers, encompassing tangibles, reliability, responsiveness, assurance, and empathy. Employing a qualitative research methodology, the investigation scrutinizes both customer and parking attendant experiences, endeavoring to discern the underlying factors contributing to service quality transgressions within the industry. The research findings underscore the pressing necessity for enhanced implementation and enforcement of consumer protection regulations, alongside the establishment of efficient complaint resolution mechanisms to address customer grievances. Furthermore, the study elucidates various factors contributing to service quality violations, including deficient training protocols, absence of licensing requirements, and ineffective regulatory frameworks. It advocates for proactive measures by policymakers and employers to rectify these issues, emphasizing the imperative of adequately training, equipping, and licensing parking attendants to ensure the delivery of exemplary service standards to customers.